How the light gets in : a novel - Maynard, Joyce, 1953- (William Morrow, an imprint of HarperCollinsPublishers, 2024)
Following the death of her former husband, Cam, fifty-four-year-old Eleanor has moved back to the New Hampshire farm where they raised three children to care for their brain-injured son, Toby, now an adult. Toby's older brother, Al, is married and living in Seattle with his wife; their sister, Ursula, lives in Vermont with her husband and two children. Although all appears stable, old resentments, anger, and bitterness simmer just beneath the surface. How the Light Gets In follows Eleanor and her family through fifteen years (2010 to 2024) as their story plays out against a uniquely American backdrop and the events that transform their world (climate change, the January 6th insurrection, school violence) and shape their lives (later-life love, parental alienation, steadfast friendship)." --